2011
DOI: 10.1007/s11422-011-9323-9
|View full text |Cite
|
Sign up to set email alerts
|

Language experience narratives and the role of autobiographical reasoning in becoming an urban science teacher

Abstract: One of the central challenges globalization and immigration present to education is how to construct school language policies, procedures, and curricula to support academic success of immigrant youth. This case-study compares and contrasts language experience narratives along Elena's developmental trajectory of becoming an urban science teacher. Elena reflects upon her early language experiences and her more recent experiences as a preservice science teacher in elementary dual language classrooms. The findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…For example, Ingersoll (2001) identified that math and science teachers have higher job dissatisfaction than other subject areas and Rinke (2009) explored the high rates of attrition for urban science teachers. Much of the research on teaching science in urban areas focuses on preparing science teachers for these challenges of teaching in urban settings, including a focus on preservice teacher experiences (e.g., Rivera Maulucci, 2011) and preparation (e.g., Chen & Mensah, 2018; Tobin et al, 1999), new science teachers (e.g., Davis et al, 2006; Marco‐Bujosa, et al, 2020), and alternative certification programs (e.g., Proweller & Mitchener, 2004). However, despite these challenges, urban schools are simultaneously sites of hope and possibilities, as Barton et al (2014) urge researchers to remember in their overview of science education in urban areas.…”
Section: Background On Urban Science Teaching and Identitymentioning
confidence: 99%
“…For example, Ingersoll (2001) identified that math and science teachers have higher job dissatisfaction than other subject areas and Rinke (2009) explored the high rates of attrition for urban science teachers. Much of the research on teaching science in urban areas focuses on preparing science teachers for these challenges of teaching in urban settings, including a focus on preservice teacher experiences (e.g., Rivera Maulucci, 2011) and preparation (e.g., Chen & Mensah, 2018; Tobin et al, 1999), new science teachers (e.g., Davis et al, 2006; Marco‐Bujosa, et al, 2020), and alternative certification programs (e.g., Proweller & Mitchener, 2004). However, despite these challenges, urban schools are simultaneously sites of hope and possibilities, as Barton et al (2014) urge researchers to remember in their overview of science education in urban areas.…”
Section: Background On Urban Science Teaching and Identitymentioning
confidence: 99%